Digital H∞ filter design for a low frequency multiple‐input multiple‐output system with multirate measurements - Yang, Hongjiu; Wang, Shuaiying; Li, Peng (International journal of robust and nonlinear control, 2022)
In this article, a digital H∞ filter is designed for a low frequency multiple‐input multiple‐output (MIMO) system with multirate measurements from multiple samplers. A delay compensation is introduced to reduce estimation errors from the multiple samplers and a zero‐order holder. A single‐rate error system is obtained by converting the low frequency MIMO system using a discrete‐time lifting technique. A digital H∞ filter is proposed based on a delay‐partitioning method to guarantee asymptotic stability and H∞ performance for the single‐rate error system. A numerical example is provided to show effectiveness and superiority of the digital H∞ filter in low frequency domain.